ON THE RATE OF WOOD LITTER DECOMPOSITION IN DRY EVERGREEN FOREST IN THE NORTHEAST OF THAILAND - Prachaiyo, Buared; Tsutsumi, Toshio (วารสารวนศาสตร์ไทย, 2022)
The study on the wood litter decomposition was carried out in a dry evergreen forest at Khon Kaen University Farm at Nam Phrom Dam. Samples were collected from six individual trees, and were kept on the forest floor. The weight of samples remaining on the floor were measured nearly one year interval for four years. Four samples among six lost more than 93% of their weight and the other one lost 83%, while the remaining one lost only 39% during four years. The rate of decomposition and factors connected to the rate were discussed.